Performance of grouted sleeve connectors in precast wall under four point load test - Siti Norzaliah , Mohd Hakimi (2014)
The need to investigate the use of precast concrete connections is a topic of growing demand. The precast structural members are normally connected via lapping of reinforcement bar. However, the large numbers of connections that are required in precast concrete system pose problems in term of strength and the failure of the connection. The application of grouted splice sleeve connectors in the market is fast gaining popularity. The adoption of existing splice sleeve connectors are not economics as these connectors in the market are proprietary and purchased from foreign country. The stability of precast concrete structure depends on the continuity between the structural member and the connection, thus the connection must exhibit the ability of transferring loads, possess sufficient strength and ductility and easy to handle and simple to erect. In this research, the connections, were the main criteria to be observed based on their performance, shear, bending and the connection failure. This research aims to develop a connection in precast wall by using different number of grouted sleeve connectors, to test the bond strength of a connection with spiral bar connectors in the wall under four point bending test and to determine the types and behavior of failure that may occur in the connection and wall panel. Based on the study conducted, the connectors were inserted in three precast wall with same size each to form one wall panel. These wall panels were tested under four point bending test in order to review the performance of the connection between the walls. In four point bending test, a uniform maximum two point loads were applied on the top of the wall panel to check the connection failure and shear failure in the wall. After tested, the results show that the grout failure occurred on the gap between the wall connections. There was deflection on the precast wall panel and no shear failure occurred at the supports. The reinforcement bar inside the steel pipe for the wall specimen with two connectors slipped before fractured.